The prevalence of lymphoid follicles and intestinal metaplasia in Helicobacter pylori associated clinically significant gastroduodenal diseases - Vildan TAŞKIN; Elif GÜRER İNANÇ; Ramazan SARI; Abdullah AYDIN; Bülent YILDIRIM; Murat ALADAĞ; Fatih HİLMİOĞLU (Turkish Journal of Gastroenterology, 2019)
-